PERTUMBUHAN LABA BANK UMUM SYARIAH DI INDONESIA: PENDEKATAN RGEC - Susan Aditya; Ibnu Muttaqin (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
This study was motivated by fluctuations in bank health indicators, such as Non-Performing Financing (NPF), which has been trending downward but remains unstable; the Capital Adequacy Ratio (CAR), which shows a downward trend despite remaining above the minimum threshold of 8%; and the inconsistent profit growth of several Islamic banks. This study aims to analyze the impact of the health indicators of Islamic Commercial Banks—using the RGEC method (NPF, GCG, ROE, and CAR)—on profit growth for the 2020–2024 period. This quantitative causal study utilizes secondary data from the annual reports of 11 Islamic Commercial Banks registered with the OJK, selected through purposive sampling. Panel data regression analysis using Eviews 13 indicates that NPF has a significant negative effect on profit growth; that is, the higher the level of non-performing financing, the lower the profit growth. Conversely, GCG, ROE, and CAR do not have a significant effect. GCG has no effect because its composite value tends to be stable; ROE only measures current-period profit ability without considering growth from the previous period; and CAR is primarily focused on meeting minimum capital requirements. The coefficient of determination indicates that the four variables together explain only 15.40% of the variation in profit growth. It is recommended that future research include additional variables, expand the sample, and extend the study period.